MECHANISMS FOR ENSURING THE BALANCE OF STATE BUDGET REVENUES AND EXPENDITURES - Sharoxmatov Abduraxim Abdulamitovich (Modern American Journals, 2025)
The effective balance between state budget revenues and expenditures is a fundamental prerequisite for ensuring fiscal stability and sustainable economic growth. This article explores the mechanisms that contribute to maintaining such a balance, including the optimization of tax and non-tax revenues, the rationalization of public spending, and the enhancement of budgetary control and treasury systems. Special attention is given to international best practices and their potential adaptation to the national context. The study also emphasizes the importance of transparency, digitalization, and performance-based budgeting in strengthening fiscal discipline. By analyzing key trends and challenges, the article provides practical recommendations for improving the efficiency of budget planning and execution.
Keywords: State budget; revenues; expenditures; fiscal balance; treasury system; budget policy; financial stability; public spending; fiscal discipline.